Laminated glass and preparation method thereof
By adopting a laminated glass structure on the windshield glass, using a combination of conductive coating, stepped metal elements and conductive cloth, the damage and electromagnetic interference problems of electrostatic discharge to the windshield glass are solved, and efficient electrostatic discharge and stability improvement are achieved.
Patent Information
- Application Number
- CN202411739051.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-28
AI Technical Summary
Existing windshield glasses are prone to electrostatic discharge in thunderstorm clouds or in high-frequency electrostatic environments, resulting in local damage and electromagnetic interference. Existing solutions such as the outer surface of conductive film plated with erosion and fall off are problems.
A laminated glass structure is adopted, in which the first layer of glass and the second layer of glass are arranged laminated. The first layer of glass is provided with a conductive coating on one side away from the second layer of glass. The edge sealing structure wraps the edge periphery of the first layer of glass, and is embedded with a stepped metal element, and the body is connected through a conductive block and a conductive cloth to achieve effective discharge of static electricity.
Through the combination of conductive blocks, stepped metal elements and conductive cloth, the stable electrical conduction state between the laminated glass and the body is ensured, which significantly improves the effect and stability of electrostatic discharge, avoids damage to the glass by electrostatic discharge, and reduces electromagnetic interference.
Smart Images

Figure CN119526849A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of traffic equipment glass or architectural glass, and in particular to a laminated glass and a method for preparing the laminated glass. Background Art
[0002] Glass is an insulating material. During the operation of an aircraft, static discharge may be generated during the contact and friction between the windshield and lightning strikes, charged particles, clouds, etc. The instantaneous high temperature and high energy may cause local damage to the windshield, such as tiny cracks and ablation points. When flying in thunderstorm clouds, lightning strikes may not only injure flight personnel, but may also damage the mechanical structure and electrical system of the aircraft. During the operation of ground high-speed rail, static discharge damages the windshield structure, affects the surrounding airflow and thus the aerodynamic performance of the train, and is also prone to electromagnetic interference with the train's signal system. The curtain wall glass of high-rise buildings in areas with frequent lightning strikes faces the same dilemma.
[0003] Currently, measures to discharge static electricity on windshields are often to coat the outer surface with a conductive film, such as a tin dioxide film, but this has the problem of easy erosion and shedding; or to perform different drainage treatments on the stepped metal elements on the edge of the glass, which cannot conduct away the static electricity accumulated on the outer glass surface and has certain limitations.
[0004] Based on the above background, it is extremely important to develop a laminated glass and a manufacturing method with efficient static discharge effect. Summary of the invention
[0005] In order to solve the problem that the existing windshield has poor static discharge effect, the present invention provides a laminated glass, comprising:
[0006] A first layer of glass, a second layer of glass, a conductive block, a stepped metal element, a conductive cloth and an edge sealing structure, wherein:
[0007] The first layer of glass and the second layer of glass are stacked;
[0008] A conductive coating is provided on a surface of the first layer of glass away from the second layer of glass;
[0009] The edge sealing structure is wrapped around the periphery of the edge of the first layer of glass;
[0010] The stepped metal element is embedded in the edge sealing structure; two ends of the stepped metal element are respectively arranged close to the first layer of glass and the second layer of glass, wherein the first end of the stepped metal element is connected to the conductive coating through the conductive block;
[0011] One end of the conductive cloth is connected to the stepped metal element inside the edge sealing structure, and the other end of the conductive cloth is located outside the edge sealing structure for connecting to the body.
[0012] In some embodiments:
[0013] The conductive block is conductive rubber, and a side of the conductive block that is in contact with the stepped metal element includes a curved surface.
[0014] In some embodiments:
[0015] The surface of the conductive block that is in contact with the stepped metal element is wavy or concave.
[0016] In some embodiments:
[0017] The conductive block is conductive rubber and has a hollow structure.
[0018] In some embodiments:
[0019] The distance H1 between the upper surface of the hollow structure close to the step-shaped metal element when installed and the side of the conductive block that is in contact with the step-shaped metal element when installed is smaller than the distance H2 between the lower surface of the hollow structure away from the step-shaped metal element when installed and the side of the conductive block that is in contact with the first layer of glass when installed.
[0020] In some embodiments:
[0021] The hollow structure includes a two-layer structure distributed along the stepped metal element toward the first layer of glass, and / or a two-layer structure distributed along one end of the first layer of glass close to the stepped metal element toward the other end away from the stepped metal element.
[0022] In some embodiments:
[0023] A groove structure or a protrusion structure is provided on the contact surface where the stepped metal element and the conductive block are attached.
[0024] In some embodiments:
[0025] A plurality of mutually parallel groove structures and / or a plurality of mutually parallel protrusion structures are provided on the contact surface between the step-shaped metal element and the conductive block.
[0026] In some embodiments:
[0027] A protruding structure is provided on the contact surface between the stepped metal element and the conductive block, and the height of the protruding structure is 1 μm to 0.1 mm.
[0028] In the laminated glass of the present invention, a conductive coating is arranged between the first layer of glass and the second layer of glass, the edge sealing structure embeds the stepped metal element, and the first end of the stepped metal element is connected to the conductive coating through the conductive block, and the second end is connected to one end of the conductive cloth, and the other end of the conductive cloth is located outside the edge sealing structure and connected to the machine body. Through the above arrangement, the first layer of glass is connected to the machine body through the action of the conductive block, the stepped metal element and the conductive cloth, so that the static electricity on the laminated glass can be eliminated, and the above structure has better stability during use, and can fully ensure the close connection between the stepped metal element and the conductive block, ensuring that the laminated glass and the machine body are in a stable electrical conduction state, so that static electricity can be discharged and the static electricity discharge effect is excellent.
[0029] The present invention also provides a method for preparing a laminated glass, which is used for processing any of the above laminated glasses, comprising:
[0030] S010: Apply a conductive coating on the side of the first layer of glass away from the second layer of glass;
[0031] S020: Composite laminating the first layer of glass and the second layer of glass;
[0032] S030: bonding a conductive block to the conductive coating;
[0033] S040: connecting the stepped metal element, the conductive block and the first layer of glass together through an edge sealing structure;
[0034] S050: bonding the conductive cloth to a preset position of the stepped metal element, and covering the conductive cloth with an isolation film;
[0035] S060: connecting the stepped metal element and the conductive cloth through the edge sealing structure and curing;
[0036] S070: removing the isolation film to obtain laminated glass.
[0037] The laminated glass prepared by the present invention connects the first layer of glass to the machine body through the functions of the conductive block, the stepped metal element and the conductive cloth, so that the static electricity on the laminated glass can be eliminated. The above structure has better stability during use and can fully ensure the close connection between the stepped metal element and the conductive block, ensuring that the laminated glass and the machine body are in a stable electrical conduction state, so it can discharge static electricity and the static electricity discharge effect is excellent. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 A schematic structural diagram of a laminated glass according to an embodiment is shown;
[0039] Figure 2 shows a cross-sectional view of a conductive block in one embodiment;
[0040] Figure 3 Another cross-sectional structural diagram of a conductive block in an embodiment is shown;
[0041] Figure 4 Another cross-sectional structural diagram of a conductive block in an embodiment is shown;
[0042] Figure 5 Another cross-sectional structural diagram of a conductive block in an embodiment is shown;
[0043] Figure 6 A schematic structural diagram of a micro-nano grid layer according to an embodiment is shown;
[0044] Figure 7 A schematic structural diagram of a micro-nano grid layer according to another embodiment is shown.
[0045] Reference numerals:
[0046] 10 is the first layer of glass, 101 is the conductive coating, 102 is the electric heating layer; 20 is the second layer of glass, 2011 is the first annular groove, 2012 is the second annular groove, 2013 is the third annular groove, 2014 is the connecting groove, 2015 is the fourth annular groove; 30 is a conductive block; 40 is a stepped metal element; 50 is a conductive cloth; 60 is an edge sealing structure, and 70 is an edge connecting structure. DETAILED DESCRIPTION
[0047] The present disclosure will now be discussed with reference to several exemplary embodiments. It should be understood that these embodiments are discussed only to enable those skilled in the art to better understand and thus implement the present disclosure, rather than implying any limitation on the scope of the present disclosure.
[0048] As used herein, the term "including" and its variants are to be interpreted as open-ended terms meaning "including but not limited to". The term "based on" is to be interpreted as "based at least in part on". The terms "one embodiment" and "an embodiment" are to be interpreted as "at least one embodiment". The term "another embodiment" is to be interpreted as "at least one other embodiment". The orientation or position relationship indicated by the terms "upper", "lower", "left", "right", "front", "back", "top", "bottom", "inner", "outer", "vertical", "horizontal", "lateral", "longitudinal" and the like is based on the orientation or position relationship shown in the accompanying drawings. These terms are mainly for better describing the present application and its embodiments, and are not used to limit the indicated devices, elements or components to have a specific orientation, or to be constructed and operated in a specific orientation. In addition, in addition to being used to indicate an orientation or position relationship, some of the above terms may also be used to indicate other meanings, such as the term "upper" may also be used to indicate a certain dependency or connection relationship in some cases. For those of ordinary skill in the art, the specific meanings of these terms in this application can be understood according to the specific circumstances. In addition, the terms "install", "set", "provided with", "connected" and "connected" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral structure; it can be a mechanical connection, or an electrical connection; it can be directly connected, or indirectly connected through an intermediate medium, or it can be an internal connection between two devices, elements or components. For those of ordinary skill in the art, the specific meanings of the above terms in this application can be understood according to the specific circumstances. In addition, the terms "first", "second", etc. are mainly used to distinguish different devices, elements or components (the specific types and structures may be the same or different), and are not used to indicate or imply the relative importance and quantity of the indicated devices, elements or components. Unless otherwise specified, "plurality" means two or more.
[0049] refer to Figure 1, is a laminated glass provided by an embodiment of the present application, comprising: a first layer of glass 10, a second layer of glass 20, a conductive block 30, a stepped metal element 40, a conductive cloth 50 and an edge sealing structure 60. The first layer of glass 10 and the second layer of glass 20 are stacked; a conductive coating 101 is provided on the surface of the first layer of glass 10 away from the second layer of glass 20; the edge sealing structure 60 is wrapped around the edge of the first layer of glass 10, and the stepped metal element 40 is embedded in the edge sealing structure 60 to limit the stepped metal element and prevent it from being displaced during use and affecting the electrical conduction between the laminated glass. The two ends of the stepped metal element 40 are respectively arranged close to the first layer of glass 10 and the second layer of glass 20, wherein the first end of the stepped metal element 40 is connected to the conductive coating through the conductive block 30. By providing the conductive block 30, the electrical connection between the stepped metal element 40 and the conductive coating 101 can be better and more stable, thereby improving the static discharge effect. The laminated glass also includes a conductive cloth 50, one end of which is connected to the stepped metal element 40 inside the edge sealing structure 60, and the other end of the conductive cloth 50 is located outside the edge sealing structure 60 for connecting to the body, thereby achieving the effect of dissipating static electricity.
[0050] In one embodiment of the present application, the conductive block 30 is conductive rubber, and a surface of the conductive block 30 that is in contact with the stepped metal element 40 includes a curved surface. In this case, during use, the elastic deformation generated by the force applied to the contact surface of the conductive block 30 and the stepped metal element 40 will be greater, which can ensure that the conductive block 30 and the stepped metal element 40 are more fully contacted.
[0051] Specifically, the side of the conductive block 30 that is in contact with the stepped metal element 40 is wavy or concave, such as Figures 2 to 3 This arrangement enables the conductive block 30 to have multiple electrical contact portions when in contact with the stepped metal element 40, and the contact area is more secure after elastic deformation, thereby improving the reliability of the electrical connection.
[0052] More specifically, Figure 2 As shown, when the above-mentioned bonding surface is wavy, it is preferred that the wavy shape has two peaks to further increase the area of the electrical contact portion.
[0053] The conductive block 30 is a conductive rubber and is a hollow structure. The hollow conductive block 30 is more likely to produce elastic deformation after being subjected to force, and the elastic deformation produced will be greater, which can ensure that the conductive block 30 and the stepped metal element 40 are attached together, and the reliability of contact is improved, thereby improving the static discharge effect. In addition, the weight of the conductive block 30 is reduced, and its deformation coordination ability when in contact with the first layer of glass 10 and the stepped metal element 40 is greatly improved, especially the curved overlap surface.
[0054] As a preferred embodiment, the distance between the upper surface of the hollow structure close to the stepped metal element 40 when installed and the side of the conductive block 30 that is in contact with the stepped metal element 40 when installed is H1, which is smaller than the distance between the lower surface of the hollow structure away from the stepped metal element 40 when installed and the side of the conductive block 30 that is in contact with the first layer of glass 10 when installed is H2, and H1<H2, such as Figure 2 As shown, when the conductive block 30 and the stepped metal element 40 are in contact, the contact surfaces of the two can be more fully deformed under the action of pressure, thereby improving the stability of the electrical contact between the two and the high efficiency of static electricity discharge.
[0055] In another embodiment of the present application, the hollow structure includes a two-layer structure (upward and downward) distributed along the stepped metal element 40 toward the first layer of glass 10, and / or a two-layer structure (leftward and rightward) distributed along one end of the first layer of glass 10 close to the stepped metal element 40 toward the other end away from the stepped metal element 40. For details, see Figures 4 to 5 .in, Figure 4 The conductive block 30 has two layers of hollow structures in both the up-down direction and the left-right direction. Figure 5 The conductive block 30 is a two-layer hollow structure in the left and right directions. The double-layer structure can further increase the elastic deformation, thereby making the fitting surface between the conductive block 30 and the stepped metal element 40 more stable and discharging static electricity more efficient.
[0056] The hollow structure may include a hollow sphere or a hollow hexahedron, or may include multiple hollow spheres or multiple hollow hexahedrons, or hollow structures having different shapes at the same time. In addition, the hollow structure of the conductive block 30 may also be set to the same structure as the outer shape structure of the conductive block 30, such as Figures 2 to 3 As shown, the cross-section of the conductive block 30 is a combination of a wavy and U-shaped structure. At this time, the hollow structure is also a wavy and U-shaped structure, but the cross-sectional direction of the hollow structure can be different from the cross-section of the conductive block 30, that is, the wavy and U-shaped structures of the hollow structure can be inverted or the like.
[0057] In one embodiment, a groove structure or a protrusion structure is provided on the contact surface where the stepped metal element 40 and the conductive block 30 are attached. That is, a groove structure or a protrusion structure is provided on one side of the stepped metal element 40 close to the conductive block 30 to improve the surface roughness of the stepped metal element 40, thereby enhancing the bonding strength between the stepped metal element 40 and the edge sealing structure 60 and the conductive adhesive contact interface.
[0058] The contact surface between the stepped metal element 40 and the conductive block 30 is provided with a plurality of mutually parallel groove structures and / or a plurality of mutually parallel protrusion structures. While improving the surface roughness of the stepped metal element 40, it is also easy to process. Of course, it is also feasible to set a plurality of mutually parallel, criss-crossed groove structures and / or protrusion structures. The present application does not specifically limit the grooves or protrusions of the other curved structures.
[0059] A protrusion structure is provided on the contact surface between the stepped metal element 40 and the conductive block 30, and the height of the protrusion structure is 1 μm to 0.1 mm to ensure the rigidity of the stepped metal element 40 and minimize the impact on its weight while improving the surface roughness of the stepped metal element 40.
[0060] In the case where the surface of the conductive block 30 in contact with the stepped metal element 40 is set to a concave-convex structure, the contact portion of the stepped metal element 40 and the conductive block 30 is set to a structure that is compatible with the first surface structure of the conductive block 30. That is, if the surface of the conductive block 30 in contact with the stepped metal element 40 is wavy, then the contact surface of the stepped metal element 40 and the conductive block 30 is set to a new wavy shape that is cross-coordinated with the crests and troughs that are compatible with the wavy shape of the conductive block 30, so as to further increase the contact area between the conductive block 30 and the stepped metal element 40 and improve the static discharge effect.
[0061] The conductive block 30 of the present application can be selected from a flexible conductive rubber with a resistance value of ≤1Ω, the rubber substrate can be selected from silicone rubber, nitrile rubber, natural rubber, and the conductive filler filled in the rubber can be selected from silver powder, silver compound, aluminum silver-plated powder, copper silver-plated powder, carbon black, nickel powder, etc., preferably a silicone rubber-based conductive rubber with good weather resistance. The stepped metal element 40 can be selected from a corrosion-resistant metal or alloy with a thickness of 0.5mm to 3mm, preferably 0.5mm to 2mm. The conductive cloth 50 can be selected from a conductive cloth with a resistance value of ≤1Ω or a flexible metal mesh-based composite fabric, such as nickel-plated conductive cloth, aluminum foil fiber composite cloth, and flexible metal mesh-based composite fabric. The length of the conductive cloth 50 is determined according to the size of the laminated glass interface to ensure sufficient electrical conduction with the body, and the length is preferably flush with the edge of the glass.
[0062] In addition, when the stepped metal element 40 and the conductive cloth 50 are arranged, there is a gap between them and the bolt holes at the edge of the laminated glass. Specifically, the gap is ≥1 mm.
[0063] The height design value of the conductive block 30 is 10% to 30% higher than the actual value of the distance between the conductive block 30 and the stepped metal element 40 to reserve sufficient contact deformation; the width of the conductive block 30 is 20% to 50% of the overlap size of the first layer of glass 10 and the stepped metal element 40, which can buffer the processing size error between the first layer of glass 10 and the stepped metal element 40 to ensure that the first layer of glass 10-conductive block 30-stepped metal element 40 can be in full electrical contact during the service of the curved laminated glass, thereby improving the reliability of the static discharge function.
[0064] The conductive block 30 can be bonded and fixed in advance to a preset position on the edge of the conductive coating surface of the first layer of glass 10 , that is, fixed to a preset position on the edge of the conductive coating surface 101 , by means of conductive adhesive.
[0065] In the laminated glass of the present invention, a conductive coating 101 is arranged between the first layer of glass 10 and the second layer of glass 20, and the edge sealing structure 60 embeds the stepped metal element 40, and the first end of the stepped metal element 40 is connected to the conductive coating 101 through the conductive block 30, and the second end is connected to one end of the conductive cloth 50, and the other end of the conductive cloth 50 is located outside the edge sealing structure 60 for connection with the machine body. Through the above arrangement, the first layer of glass 10 is connected to the machine body through the functions of the conductive block 30, the stepped metal element 40 and the conductive cloth 50, so as to realize the static electricity discharge path, thereby being able to eliminate the static electricity on the laminated glass, and the above structure has better stability during use, and can fully ensure the close connection between the stepped metal element 40 and the conductive block 30, ensuring that the laminated glass and the machine body are in a stable electrical conduction state, so that static electricity can be discharged and the static electricity discharge effect is excellent. The combination of the conductive coating 101, the conductive block 30, the stepped metal element 40 and the conductive cloth 50 can suppress the electrostatic discharge noise of the laminated glass, better solve the problem of the outer surface conductive film being easily washed off during service, and achieve the effect of efficient static discharge.
[0066] In addition, the laminated glass of the present application also includes a conductive and magnetic composite micro-nano grid layer arranged on the surface of the second layer of glass 20 and located between the first layer of glass 10 and the second layer of glass 20 to achieve low electromagnetic and low interference functions.
[0067] The micro-nano grid layer is set to an irregular pattern without diffraction to eliminate moiré fringes and achieve a comfortable visual experience. In addition, the micro-nano grid layer is led out from the end of the second layer of glass 20 to form a lead-out part for connecting the frame body, so as to achieve electrical conduction between the laminated glass and the body, thereby better achieving the effects of low interference, low detection and static discharge.
[0068] The above-mentioned micro-nano grid layer is directly embossed on the surface of the laminated glass middle layer film, with a resistance of ≤1Ω, preferably 0.1~0.5Ω, and has electromagnetic shielding performance for low-frequency bands (≤30Mhz). The micro-nano grid layer is preferably a conductive and magnetic composite slurry doped with magnetic materials to achieve excellent electromagnetic shielding performance for both electric and magnetic fields, so that the laminated glass can achieve the best low-interference effect on personnel or equipment that need protection. Specifically, the molar ratio of the doping amount of magnetic material in the conductive and magnetic composite slurry is 5% to 20%. Among them, the conductive filler can be selected from silver powder, gold powder, copper powder, silver-coated copper powder, platinum powder, etc., and the magnetic filler can be selected from nickel powder, iron powder, iron silicon aluminum powder, iron nickel powder, cobalt powder, beryllium molybdenum alloy powder, etc. In the optimal embodiment of the present application, the conductive filler is preferably silver powder with good ductility and high cost performance, and the magnetic filler is preferably beryllium molybdenum alloy powder with high magnetic permeability to achieve the best conductive and magnetic effect.
[0069] The micro-nano grid layer needs to be electrically conductive with the machine body to ensure that the electromagnetic signal interference outside the laminated glass is reduced to a minimum and achieve the best electromagnetic shielding performance. Therefore, the micro-nano grid layer is led out from the end of the second layer of glass 20 to form a lead-out portion for connecting to the frame. The length of the lead-out portion is determined according to the interface size of the laminated glass, and extends to the connection portion between the laminated glass and the frame to ensure electrical conductivity with the frame.
[0070] In one embodiment of the present application, the micro-nano grid layer includes a plurality of connected curved grooves, and at least two of the grooves have different shapes and / or sizes.
[0071] In a specific embodiment, the shape of the groove is preferably an arc, and the outer walls of two adjacent grooves are tangent to each other, thereby avoiding the occurrence of stress concentration and making the laminated glass have good mechanical properties.
[0072] Specifically, the groove includes a first annular groove 2011 and a second annular groove 2012 located in the first annular groove 2011. The multiple annular groove structures are densely arranged, so that the force on the surface of the laminated glass is more balanced, and the service life of the laminated glass is improved. Preferably, at least two second annular grooves 2012 are arranged in the first annular groove 2011 to further disperse the force on the surface of the laminated glass.
[0073] In a specific embodiment, two adjacent first annular grooves 2011 are connected via a connecting groove 2014 to further balance the surface stress of the laminated glass.
[0074] Preferably, a third annular groove 2013 is arranged between adjacent connecting grooves 2014, and the connecting groove 2014 is located between the third annular groove 2013 and the first annular groove 2011. When at least three first annular grooves 2011 are closed and connected in sequence through the connecting groove 2014 to form a new annular groove structure, the third annular groove 2013 can be preferably arranged in the new annular groove structure. This allows the surface force of the laminated glass to be evenly dispersed, thereby improving the force bearing capacity and durability of the laminated glass. At least two second annular grooves 2012 are arranged in the first annular groove 2011, and two adjacent second annular grooves 2012 are arranged in an external manner, and the sizes and structures of different second annular grooves 2012 are allowed to be not completely the same. Further, the second annular groove 2012 distributed close to the first annular groove 2011 is preferably inscribed in the first annular groove 2011. The annular groove structures are mutually embedded, and while eliminating the moiré fringes, stress is further eliminated, thereby improving the force bearing capacity of the laminated glass.
[0075] See also Figure 6 , is a preferred embodiment of the present application, wherein four second annular grooves 2012 of the same size and structure are arranged in the first annular groove 2011, two adjacent second annular grooves 2012 are circumscribed, and the four second annular grooves 2012 are all inscribed in the first annular groove 2011. It can be seen that the four adjacent first annular grooves 2011 are closed and connected in sequence through the connecting groove 2014. At this time, the connecting groove 2014 is preferably a minor arc, and the two ends of the minor arc are respectively inscribed in the two adjacent first annular grooves 2011. In this embodiment, after the four adjacent first annular grooves 2011 are closed and connected in sequence through the connecting groove 2014, a new annular groove structure is formed in the middle thereof, such as Figure 6 As shown, the third annular groove 2013 is located in the new annular groove structure. In this embodiment, four third annular grooves 2013 are provided, and adjacent third annular grooves 2013 are circumscribed and inscribed in the new annular groove structure. Specifically, the size of the new annular groove structure is smaller than the first annular groove 2011.
[0076] The above-mentioned first annular groove 2011, second annular groove 2012 and third annular groove 2013 can be optionally set as circular annular grooves or elliptical annular grooves, etc., and when the first annular groove 2011 is a circular annular groove, the second annular groove 2012 and / or the third annular groove 2013 can be set as different annular groove structures.
[0077] See also Figure 7, which is another preferred embodiment of the present application, the groove includes a first annular groove 2011, a second annular groove 2012 and a fourth annular groove 2015; the second annular groove 2012 is located in the first annular groove 2011 and is provided with at least two; at least one fourth annular groove 2015 is circumscribed with one of the two adjacent first annular grooves 2011, intersects with the other first annular groove 2011 and is circumscribed with at least one second annular groove 2012 located inside it. Preferably, the shape of the fourth annular groove 2015 is elliptical, and when the elliptical fourth annular groove 2015 connects two adjacent first annular grooves 2011, it is circumscribed with one of the first annular grooves 2011, intersects with the other first annular groove 2011 and is circumscribed with at least one second annular groove 2012 inside it. Preferably, the elliptical fourth annular groove 2015 connects the two adjacent first annular grooves 2011 in the direction of the minor axis of the ellipse, and the two adjacent first annular grooves 2011 are circumscribed in the direction of the major axis. At this time, at least two second annular grooves 2012 can also be provided inside the first annular groove 2011. Here, five second annular grooves 2012 are provided as an example. Figure 7 As shown, when the five second annular grooves 2012 are arranged, one of them is located at the center of the first annular groove 2011, and the other four are distributed circumferentially around the second annular groove 2012 at the center and are simultaneously inscribed with the first annular groove 2011 and circumscribed with the second annular groove 2012 at the center. At this time, the fourth annular groove 2015 is circumscribed with the two second annular grooves 2012 away from the center. Figure 7 Preferably, the maximum dimension between two points on the first annular groove 2011 is greater than the dimension of the major axis of the ellipse.
[0078] The first annular groove 2011, the second annular groove 2012, the third annular groove 2013, the connecting groove 2014 or the fourth annular groove 2015 may also be distributed in other ways. For example, according to the size of the first annular groove 2011, a plurality of second annular grooves 2012 may be arranged therein and distributed in an annular periphery or in a straight line within the first annular groove 2011. Of course, the distribution method is not limited to the above structure.
[0079] In particular, the mesh pattern on the micro-nano mesh layer is preferably a pattern of an alternating combination of embedded closed circular rings, open or closed ellipses, so as to enhance the deformation capacity of the mesh, meet the integrity of the mesh structure under the action of wind pressure and aerodynamic load, and reduce the risk of its breakage. The embedded closed circular ring is preferably embedded with four or five circular rings. In addition, a mesh pattern with other patterns or distribution methods can also be used.
[0080] When the above-mentioned micro-nano grid layer is a micro-nano grid layer, it is manufactured by nanoimprinting process. In addition to conventional polyethylene terephthalate (PET), the attached substrate is preferably an intermediate layer material commonly used in laminated glass, such as polyurethane film, polyvinyl butyral film, ethylene-vinyl acetate copolymer (EVA), ion-type intermediate film (SGP), etc., so as to achieve the compatibility of the micro-nano grid layer with flat and curved laminated glass.
[0081] In a preferred embodiment of the present application, a silver nanowire coating is provided on a side of the first layer of glass 10 away from the second layer of glass 20 to improve the static electricity dissipation effect of the laminated glass.
[0082] The above-mentioned silver nanowire coating is directly exposed to the outdoor environment, and the resistance reaches 1MΩ~100MΩ to achieve the static discharge function. The silver nanowire coating includes silver nanowires, siloxane coatings or polyurethane coatings doped with conductive metals or metal oxide particles, poly (3,4-ethylenedioxythiophene)-polystyrene sulfonic acid, etc. The influence of the metal doping amount on the coating resistance and transmittance is mutually restricted. Under the condition of constant resistance, the optical properties of the coating are improved as the diameter of the doped material decreases and the length increases. In this embodiment, the doped conductive material is a silver nanowire with an aspect ratio of ≥500, preferably an aspect ratio of ≥1500, and the molar ratio of the doping amount is 1%~10%, preferably 1%~7%. The small diameter of the silver nanowires at the micro-nano scale improves the transmittance, and the high length realizes good internal self-electrical lap.
[0083] In one embodiment, a conductive coating 101 having a three-layer structure is provided on one side of the first layer of glass 10 away from the second layer of glass 20, and the low-detection film, dielectric film, and silver nanowire coating are arranged in order from the side close to the first layer of glass 10 to the side away from the first layer of glass 10. The setting of the above-mentioned low-detection film realizes the low-detection function, the dielectric film realizes the protection of the low-detection film, and the outermost silver nanowire coating realizes the static discharge effect, and further protects the low-detection film. The low-detection film is a low-resistance transparent conductive film, and gold film (Au), silver film (Ag), indium tin oxide film (ITO), aluminum-doped zinc oxide (AZO), zinc oxide (ZnO), nanoparticle-doped metal film, etc. can be selected, and a single-layer or multi-layer conductive film is composited, and the film layer resistance is preferably ≤30Ω to realize the low-detection function. In order to protect the low-detection film, the dielectric film can be selected from single-layer or multi-layer combination films such as silicon dioxide (SiO2) film, silicon nitride (SiNx) film, aluminum oxide (Al2O3) film, titanium oxide (TiO2) film, transparent diamond-like carbon (DLC) film, and magnesium fluoride (MgF2). The film material and thickness are designed with the help of optical software to obtain the best optical performance.
[0084] In the embodiment of the present application, according to the use requirements, an electric heating layer 102 can be provided on the side of the first layer of glass 10 close to the second layer of glass 20 to realize the function of electric heating.
[0085] In one embodiment of the present application, a third layer of glass is further included between the first layer of glass 10 and the second layer of glass 20 , and the micro-nano grid layer is disposed on a side of the third layer of glass 20 away from the first layer of glass 10 .
[0086] See also Figure 1 , which is a laminated glass with a three-layer glass structure. At this time, the micro-nano grid layer is arranged on a side of the third layer of glass 20 away from the first layer of glass 10 and is directly embossed on the film surface on the third layer of glass 20.
[0087] In a specific embodiment, electromagnetic simulation or actual measurement methods can be used to adjust the position of the micro-nano grid layer in the laminated glass so that the electromagnetic wave reaches the best loss between the first layer of glass 10 and the micro-nano grid layer. The position of the micro-nano grid layer can be between the first layer of glass 10 and the second layer of glass 20, or between the second layer of glass 20 and the third layer of glass. A laminated glass provided in an embodiment of the present application has a micro-nano grid layer located between the first layer of glass 10 and the second layer of glass 20 on the surface of the second layer of glass 20, which connects the laminated glass and the frame. The composite characteristics of the conductive and magnetic properties of the above-mentioned micro-nano grid layer realize the function of low electromagnetic anti-interference, thereby making the laminated glass have the characteristics of low detectability and low interference during use.
[0088] The present application sets a conductive coating 101 including a low-detection film, a dielectric film, and a silver nanowire coating on the outer surface of the first layer of glass 10 of the laminated glass to achieve low-detection and static discharge functions; a conductive and magnetic micro-nano grid layer is set on the surface of the second layer of glass 20 to achieve electromagnetic shielding function. Both the conductive coating 101 and the micro-nano grid layer are electrically connected to the body to form a parallel effect, thereby enhancing the low-detection and low-interference performance of the laminated glass. An electric heating layer 102 can be added to the inner surface of the first layer of glass 10 as needed, thereby meeting multiple requirements of the transportation equipment or architectural glass field for laminated glass stealth, electromagnetic shielding, static discharge, electric heating, etc.
[0089] In addition, the present application also provides a method for preparing a silver nanowire coating. In order to reduce the encapsulation of the morphology control agent during the synthesis of the silver nanowires, increase their insulation and reduce their conductivity, a polyol method is preferably used to prepare silver nanowires with a high aspect ratio. Specifically, the polyol is preferably propylene glycol or ethylene glycol with good volatility. The preparation method is as follows:
[0090] S100: (0.2±0.1) mol of AgNO3 as precursor, ethylene glycol as solvent, (0.2±0.1) mol of Fe(NO3)3, (2.2±1) mol of NaCl, etc. were added and mixed;
[0091] In the embodiments of the present application, in order to improve the aspect ratio of silver nanowires and prevent Ag+ from generating silver nanoparticles and multiple twins, a weak oxidant such as Fe3+ with a molar ratio of 0.8 to 0.3 and an inhibitor such as Cl- with a molar ratio of 0.02 to 0.005 are added.
[0092] S200: reacting at a constant temperature of 80°C to 120°C for (3±1) h to obtain a silver nanowire solution with an aspect ratio of ≥500;
[0093] The aspect ratio of the silver nanowire solution is preferably ≥1500. In a preferred embodiment of the present application, the reaction is carried out at a constant temperature of 80°C to 120°C for (3±1) hours to obtain a silver nanowire solution with an average length of 90.1 μm to 70 μm and an average diameter of 48.2 nm to 20 nm. The small diameter of the silver nanowire improves the transmittance, and the long length achieves good internal self-electrical bonding.
[0094] S300: filtration to obtain pure silver nanowires;
[0095] S400: adding 1% to 10% of silver nanowires into the polysiloxane solution, blending, and obtaining a polysiloxane conductive coating, namely, a silver nanowire coating.
[0096] In a preferred embodiment, 1% to 7% of silver nanowires are added to a polysiloxane solution and blended to obtain a silver nanowire coating.
[0097] The prepared silver nanowire coating is sprayed on the outer surface of the first layer of glass 10 away from the second layer of glass 20 by a spraying process, and cured for (2±0.5) hours in an environment of 80°C to 150°C, so that its resistance reaches (1 to 30) MΩ and its haze is ≤2.5%.
[0098] In one embodiment of the present application, a method for preparing a laminated glass is further provided, which is used for processing the laminated glass, comprising:
[0099] S010: coating a conductive coating 101 on a side of the first layer of glass 10 away from the second layer of glass 20;
[0100] If necessary, an electric heating layer 102 may be coated on the inner surface of the first layer of glass 10 close to the second layer of glass 20 to meet the requirement of electric heating.
[0101] S020: Composite lamination of the first layer of glass 10 and the second layer of glass 20;
[0102] After the coating of each layer of glass is completed, the first layer of glass 10 and the second layer of glass 20 are compounded.
[0103] S030: bonding the conductive block 30 to the conductive coating 101;
[0104] S040: Connecting the stepped metal element 40, the conductive block 30 and the first layer of glass 10 together through the edge sealing structure 60;
[0105] At this time, the edge sealing structure 60 needs to be glued between the laminated glasses with the help of a mold so that the positions between the stepped metal element 40, the conductive block 30 and the first layer of glass 10 are relatively fixed, and the mold is removed after solidification. If the conductive block 30 is conductive rubber, the conductive rubber is protected before gluing to prevent it from being glued and solidified with the edge sealing structure 60 and affecting elastic deformation during use.
[0106] S050: bonding the conductive cloth 50 to a preset position of the stepped metal element 40, and covering the conductive cloth 50 with an isolation film;
[0107] S060: connecting the stepped metal element 40 and the conductive cloth 50 through the edge sealing structure 60 and curing;
[0108] This step still requires the use of a mold to ensure that the glue is in place and to play a certain drainage and limiting role on the glue to prevent it from affecting the structure and normal use of the laminated glass after solidification.
[0109] S070: removing the isolation film to obtain laminated glass.
[0110] At this point, a laminated glass that achieves edge electrical connection, sealing protection, and includes electrostatic conduction and drainage components has been prepared.
[0111] The laminated glass prepared by the present invention connects the first layer of glass to the machine body through the functions of the conductive block, the stepped metal element and the conductive cloth, so that the static electricity on the laminated glass can be eliminated. The above structure has better stability during use and can fully ensure the close connection between the stepped metal element and the conductive block, ensuring that the laminated glass and the machine body are in a stable electrical conduction state, so it can discharge static electricity and the static electricity discharge effect is excellent.
[0112] In a processing example of the laminated glass of the present application, an electric heating layer 102 is plated on the inner surface of the first layer of glass 10 near the second layer of glass 20, and then the first layer of glass 10 is turned over, and a low-detection film and a dielectric film are plated on the outer surface of the first layer of glass 10 in turn. In this embodiment, the low-detection film material is selected from an indium tin oxide composite film with a resistance of (15±10)Ω, and the dielectric film is selected from silicon dioxide. Then, a silver nanowire coating is sprayed on the dielectric film, and after curing, its resistance reaches (10~50)MΩ. The surface of the second layer of glass 20 is plated with a micro-nano grid layer of silver-nickel alloy slurry, with a resistance of (0.5±0.3)Ω, and the micro-nano grid layer is attached to a polyurethane film. Before lamination, the micro-nano grid layer is cut to a size that can be connected to the frame. The first layer of glass 10, the second layer of glass 20, and the connecting materials for the edge structure support of the bolt structure are laminated to obtain laminated glass.
[0113] The lead-out part of the micro-nano grid layer 201 is bonded and fixed on the edge of the outer surface of the laminated glass, and the step-shaped metal element 40 is connected with the conductive block 30 and the first layer of glass 10 by using the edge sealing structure 60; the sealant is applied to the end face of the laminated glass by means of the mold by the pouring or molding method again, and then solidified and demolded; then the conductive cloth 50 of the preset size is bonded and fixed at the appropriate position on the step-shaped metal element 40; finally, the lead-out part of the micro-nano grid layer 201 is extended to the lower edge of the laminated glass close to the frame side and fixed, and the obtained laminated glass is fixedly installed with the body through the edge connection structure. The laminated glass containing low detection, low interference and static discharge combination components obtained by the above processing has a light transmittance of ≥70%, and the laminated glass has a good electromagnetic shielding effect in an electric field environment.
[0114] Low-detection films and dielectric films are preferably prepared using magnetron sputtering technology to adapt to the preparation of large-sized and special-shaped samples. Small-sized samples can be prepared using chemical vapor deposition (CVD) or physical vapor deposition (PCVD).
[0115] The silver nanowire coating for dissipating static electricity can be applied to the outer surface of the first layer of glass 10 by spraying, spin coating, blade coating, dip coating or other processes, and then cured by heating to form a film.
[0116] According to the above technical solution, the laminated glass structure and preparation method including low detection, low interference and static discharge combination components proposed in the embodiment of the present application have at least the following advantages:
[0117] 1. The conductive coating 101 on the outer surface of the first layer of glass 10, the electric heating layer 102 on the inner surface of the first layer of glass 10, the micro-nano grid layer on the second glass layer 20 and other materials and combined structures of the present application realize the comprehensive functions of laminated glass such as low detection, low interference, static electricity discharge, and electric heating, and provide solutions for window products serving in special environments.
[0118] 2. The conductive coating 101 on the outer surface of the first layer of glass 10 of the present application adopts a low-detection film-dielectric film-silver nanowire coating structure from the inside out, which on the one hand realizes the low-detection and static discharge functions of the laminated glass, and on the other hand improves the reliability of the low-detection film on the outer surface of the laminated glass.
[0119] 3. The micro-nano mesh layer of the present application is preferably a micro-nano mesh layer of a conductive and magnetic composite slurry with a resistance of ≤1Ω, which can expand the electromagnetic shielding effectiveness in the low-frequency band (≤30Mhz) relative to the transparent conductive film.
[0120] 4. The low-detection, low-interference material of the present application and the body electrical conductive connection material and structure can form a parallel effect, thereby improving the low-detection, low-interference performance of the laminated glass.
[0121] Those skilled in the art will appreciate that the above-mentioned embodiments are specific examples for implementing the present disclosure, and in actual applications, various changes may be made thereto in form and detail without departing from the scope of the present disclosure.
Claims
1. A laminated glass, characterized in that: include: A first layer of glass (10), a second layer of glass (20), a conductive block (30), a stepped metal element (40), a conductive cloth (50) and an edge sealing structure (60), wherein: The first layer of glass (10) and the second layer of glass (20) are stacked; A conductive coating (101) is provided on a surface of the first layer of glass (10) away from the second layer of glass (20); The edge sealing structure (60) is wrapped around the periphery of the edge of the first layer of glass (10); The stepped metal element (40) is embedded in the edge sealing structure (60); two ends of the stepped metal element (40) are respectively arranged close to the first layer of glass (10) and the second layer of glass (20), wherein the first end of the stepped metal element (40) is connected to the conductive coating (101) via the conductive block (30); One end of the conductive cloth (50) is connected to the stepped metal element (40) inside the edge sealing structure (60), and the other end of the conductive cloth (50) is located outside the edge sealing structure (60) for connection to the machine body.
2. The laminated glass according to claim 1, characterized in that: The conductive block (30) is conductive rubber, and a surface of the conductive block (30) that is in contact with the stepped metal element (40) includes a curved surface.
3. The laminated glass according to claim 2, characterized in that: The surface of the conductive block (30) that is in contact with the stepped metal element (40) is wavy or concave.
4. The laminated glass according to claim 1, characterized in that: The conductive block (30) is conductive rubber, and the conductive block (30) is a hollow structure.
5. The static dissipation laminated glass according to claim 4, characterized in that: A distance H1 between an upper surface of the hollow structure close to the step-shaped metal element (40) when installed and a side of the conductive block (30) that is in contact with the step-shaped metal element (40) when installed is smaller than a distance H2 between a lower surface of the hollow structure away from the step-shaped metal element (40) when installed and a side of the conductive block (30) that is in contact with the first layer of glass (10) when installed.
6. The laminated glass according to claim 4, characterized in that: The hollow structure comprises a two-layer structure distributed along the stepped metal element (40) toward the first layer of glass (10), and / or a two-layer structure distributed along one end of the first layer of glass (10) close to the stepped metal element (40) toward the other end away from the stepped metal element (40).
7. The laminated glass according to claim 1, characterized in that: A groove structure or a protrusion structure is provided on the contact surface where the stepped metal element (40) and the conductive block (30) are in contact.
8. The laminated glass according to claim 7, characterized in that: A plurality of mutually parallel groove structures and / or a plurality of mutually parallel protrusion structures are provided on the contact surface between the stepped metal element (40) and the conductive block (30).
9. The laminated glass according to claim 7, characterized in that: A protruding structure is provided on the contact surface between the stepped metal element (40) and the conductive block (30), and the height of the protruding structure is 1 μm to 0.1 mm.
10. A method for preparing laminated glass, for processing the laminated glass according to any one of claims 1 to 9, characterized in that: include: S010: coating a conductive coating (101) on a side of the first layer of glass (10) away from the second layer of glass (20); S020: Composite-laminate the first layer of glass (10) and the second layer of glass (20); S030: bonding the conductive block (30) onto the conductive coating (101); S040: connecting the stepped metal element (40), the conductive block (30), and the first layer of glass (10) together via an edge sealing structure (60); S050: bonding the conductive cloth (50) to a preset position of the stepped metal element (40), and covering the conductive cloth (50) with an isolation film; S060: connecting the stepped metal element (40) and the conductive cloth (50) via the edge sealing structure (60), and curing; S070: removing the isolation film to obtain laminated glass.